Coronavirus disease 2019 in patients with cardiovascular disease: clinical features and implications on cardiac biomarkers assessment. Issue 11 (3rd November 2021) - Arcari, Luca; Luciani, Michelangelo; Cacciotti, Luca; Pucci, Mariateresa; Musumeci, Maria Beatrice; Pietropaolo, Lorenzo; Spuntarelli, Valerio; Negro, Andrea; Camastra, Giovanni; Bentivegna, Enrico; Marazzi, Giuseppe; Sighieri, Cinzia; et al.
Abstract : Introduction: Previous cardiovascular disease (CVD) and myocardial involvement are common in coronavirus disease-19 (COVID-19). We investigated relationships between CVD, cardiac biomarkers and outcome in COVID-19. Methods: We analyzed n = 252 patients from a multicenter study and provided comparison according to the presence or absence of underlying CVD. Cardiac biomarkers high-sensitivity Troponin [upper reference of normality (URN) 35 pg/ml for Troponin I and 14 pg/ml for Troponin T] and natriuretic peptides (Nt-pro-B-type natriuretic peptide, URN 300 pg/ml and B-type natriuretic peptide, URN 100 pg/ml) were both available in n = 136. Results: Mean age was 69 ± 16 years (56% men, 31% with previous CVD). Raised hs-Troponin and natriuretic peptides were detected in 36 and 50% of the cases respectively. Age, chronic obstructive pulmonary disease, hemoglobin, hs-Troponin and natriuretic peptides were independently associated with underlying CVD ( P < 0.05 for all). Compared with the normal biomarkers subgroups, patients with isolated hs-Troponin elevation had higher in-hospital mortality (31 vs. 4%, P < 0.05), similar CVD prevalence (15 vs. 11%) and trend towards higher D-dimer (930 vs. 397 ng/ml, P = 0.140). Patients with both biomarkers elevated had higher age, D-dimer, CVD and in-hospital mortality prevalence compared with other subgroups (all P < 0.05 for trend). Outcome analysis revealed previous CVD [model 1: OR 2.72 (95% CI 1.14–6.49), P = 0.024. model 2: OR 2.65 (95% CI 1.05–6.71), P = 0.039], hs-Troponin (log10 ) [OR 2.61 (95% CI 1.21–5.66), P = 0.015] and natriuretic peptides (log10 ) [OR 5.84 (95%CI 2.43–14), P < 0.001] to be independently associated with in-hospital mortality. Conclusion: In our population, previous CVD was part of a vulnerable phenotype including older age, comorbidities, increased cardiac biomarkers and worse prognosis. Patients with isolated increase in hs-Troponin suffered higher mortality rates despite low prevalence of CVD, possibly explained by higher COVID-19-related systemic involvement.